More Pain, Less Strength: Higher Pain is Associated with Lower Knee Extensor Strength in Adolescents with Patellofemoral Pain—a Cross-Sectional Study - Samual A. Kayll; Rana S. Hinman; Adam L. Bryant; Kim L. Bennell; Fiona McManus; Patrick L. Rowe; Kade L. Paterson (Medicine & Science in Sports & Exercise, 2026)
Objectives: Assess differences in lower limb strength between adolescents with and without patellofemoral pain (PFP) and explore the association between strength and pain in adolescents with PFP. Design: Cross-sectional. Methods: One hundred and two male and female (n=24) adolescents aged 12-19 (mean=17 years ± 2) participated in this cross-sectional study (n=51 with PFP and n=51 age- and sex-matched controls). Strength was measured as peak isometric torque (Nm) using an isokinetic dynamometer during knee extension/flexion, and ankle plantar flexion. The worst pain in the previous week was rated on an 11-point numerical rating scale (0=no pain, 10=worst pain imaginable). Differences in strength between participants with and without PFP, as well as associations between strength measures and pain in adolescents with PFP, were investigated using separate linear regression models, unadjusted and adjusted for age, sex, and body weight. Results: Adjusted mean (95% confidence interval [CI]) knee extension strength was 18.2 (3.6-32.8)Nm less in adolescents with PFP than in controls. For every one-point increase in pain, there was a mean (95% CI) adjusted reduction of 8.0 (15.4-0.6)Nm and an unadjusted reduction of 12.6 (23.5-1.7)Nm of knee extension torque in the PFP group. There were no between-group differences or associations between strength and pain for the other strength measures. Conclusions: Adolescents with PFP may have lower knee extension strength than their pain-free counterparts. Higher pain may be associated with lower knee extension strength in adolescents with PFP. Future research may investigate whether increases in knee extension strength in adolescent PFP mediate improvements in pain.